Membedah Kasus Penistaan Agama oleh sang Murtad Kace - Mei Rahmawati (Ar-Raniry: International Journal of Islamic Studies, 2022)
In August 2021, Indonesia was shocked by the blasphemy incident by an Indonesian YouTuber. It is not surprising that this religious blasphemy exists because it often happens in Indonesia over and over again. Uniquely, the name of this religious blasphemer has the initials MK, which begins with the name of "Muhammad" aka Muhammad Kace by dressing like a cleric, wearing black caps, and attracting netizens to upload his YouTube account with many controversial statements. Another uniqueness is that Kace is a religious blasphemer as well as an apostate. Perhaps we know that a religious blasphemer publicly proclaimed his apostasy to the public in his material posted on YouTube in 2014. In this article, we will find out what the phenomenon of blasphemy by Kace is, and what the Islamic perspective is in that context.